2021
DOI: 10.1007/s40618-021-01535-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency, secondary hyperparathyroidism and respiratory insufficiency in hospitalized patients with COVID-19

Abstract: Purpose Hypovitaminosis D has emerged as potential risk factor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the general population with variable effects on the outcome of the coronavirus disease-19 (COVID-19). The aim of this retrospective single-center study was to investigate the impact of hypovitaminosis D and secondary hyperparathyroidism on respiratory outcomes of COVID-19. Methods Three-hundred-forty-eight consecutive patients hospitalized for COVID-19 at the IRCCS Humani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
1
11
0
11
Order By: Relevance
“…Our findings are in agreement with previously published studies showing a high prevalence of hypovitaminosis D and hypocalcemia in COVID-19 patients concomitantly with a low rate of secondary hyperparathyroidism. Hernández [26]; finally, a very recent study reported PTH levels slightly above the normal range (mean level 63.5 pg/mL) in COVID-19 patients with VD levels below 20 ng/mL [27].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our findings are in agreement with previously published studies showing a high prevalence of hypovitaminosis D and hypocalcemia in COVID-19 patients concomitantly with a low rate of secondary hyperparathyroidism. Hernández [26]; finally, a very recent study reported PTH levels slightly above the normal range (mean level 63.5 pg/mL) in COVID-19 patients with VD levels below 20 ng/mL [27].…”
Section: Discussionmentioning
confidence: 94%
“…Our hypothesis was based on the accepted notion that vitamin D (VD) is a crucial hormone for calcium homeostasis increasing intestinal calcium and phosphate absorption [19] and on the high prevalence of VD deficiency in COVID-19 patients reported by several studies [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D became known as a natural immunomodulatory compound (62); hence, its levels should be promptly assessed in COVID-19 patients and supplementation should be started if necessary. Vitamin D level was linked to clinical outcomes in COVID-19 (63). General nutrition status which is commonly hampered in hypercortisolemic subjects can be tied to final outcomes as wellthe higher the nutrition risk, the worse the prognosis in COVID-19 (64).…”
Section: Special Circumstance: Hypercortisolemic Patient With Covid-19mentioning
confidence: 99%
“…I valori di PTH sono stati, invece, valutati in 97 pazienti ed è emerso che i pazienti con iperparatiroidismo secondario, indipendente dai livelli di 25-OH vitamina D, erano più frequentemente esposti all'insorgenza di insufficienza respiratoria acuta (p = 0,001) e richiedevano più frequentemente il ricorso alla ventilazione (p = 0,031) rispetto a pazienti con valori normali di PTH. In tal senso, è possibile ipotizzare che il PTH possa svolgere un ruolo indipendente nell'evoluzione della polmonite da SARS-CoV-2, possibilmente mediato dagli effetti pleiotropici del PTH sul processo infiammatorio e sulla performance cardio-respiratoria [29].…”
Section: Covid-19 E Ipovitaminosi Dunclassified
“…Tutto ciò impone di prestare particolare attenzione a questa categoria di pazienti, anche se con sintomi di infezione moderati, e di riservare particolare interesse al controllo glicemico. Maggior rischio di mortalità e malattia severa in pazienti con peggiore controllo glicemico [21] Farmacoterapia in diabete mellito Minore ricorso alla ventilazione invasiva e ridotta mortalità nei pazienti diabetici in trattamento con DPP4 inibitori [16] Migliore outcome in chi è in farmacoterapia con metformina rispetto ai pazienti in terapia con altri farmaci [19] Vitamina D Il deficit di vitamina D si associa a forme più severe di infezione da SARS-Cov-2, a maggior rischio di ospedalizzazione e a maggiore mortalità [26] Deficit di vitamina D Ridotti livelli di vitamina D peggiorano la prognosi della malattia da SARS-Cov-2, indipendentemente dalla presenza di comorbidità [28] Ridotti livelli di vitamina D possono determinare un maggior rischio di contrarre l'infezione da SARS-Cov-2 [27] Iperparatiroidismo secondario Il PTH ha un ruolo indipendente sull'evoluzione della polmonite da SARS-Cov-2: i pazienti con iperparatiroidismo secondario sono più frequentemente esposti all'insorgenza di insufficienza respiratoria acuta [29] Terapia con vitamina D La supplementazione di vitamina D in pazienti con infezione da SARS-Cov-2 riduce la severità della malattia [31] In relazione al ruolo svolto dalla vitamina D nella regolazione del sistema immunitario si può concludere che i soggetti con livelli deficitari della stessa sono esposti a un maggiore rischio di contrarre l'infezione da SARS-CoV-2, a quadri polmonari più severi e a una maggiore mortalità correlata. Saranno necessari, invece, ulteriori studi per chiarire il ruolo della supplementazione di vitamina D in tali pazienti, in quanto i trials sinora condotti hanno mostrato risultati contrastanti.…”
Section: Conclusioniunclassified